Synchrotron FT-IR microspectroscopic analysis of necrotic bone. Issue 4 (2007) - Bayarı Bayarı, Sevgi Haman Sevgi Haman; Utku Utku, Haluk Haluk; Ikemoto Ikemoto, Yuka Yuka; Celasun Celasun, Bülent Bülent; Kömürcü Kömürcü, Mahmut Mahmut; Atik Atik, Aziz Aziz
Abstract : Avascular necrosis (osteonecrosis) is a disease that results from the temporary or permanent loss of blood supply to the bone. Synchrotron FT-IR microspectroscopy has been used to study the changes in mineral and matrix content of necrotic bone. FT-IR spectroscopic analysis revealed that in necrotic bone the relative mineral/matrix ratio decreased. Spectroscopic differences were observed between normal and necrotic bones. The noticeable differences may have important implications for analyzing and evaluating death bone.